Seismological and mineralogical studies of the world’s deepest gold-bearing horizon, the Carbon Leader Reef, West Wits Line goldfields (South Africa): implications for its poor seismic reflective character - Nkosi, Nomqhele Zamaswazi (My University, 2016)
The measurements of physical rock properties, seismic velocities in particular, associated with ore deposits and their host rocks are crucial in interpreting seismic data collected at the surface for mineral exploration purposes. The understanding of the seismic velocities and densities of rock units can help to improve the understanding of seismic reflections and thus lead to accurate interpretations of the subsurface geology and structures. This study aims to determine the basic acoustic properties and to better understand the nature of the seismic reflectivity of the world’s deepest gold-bearing reef, the Carbon Leader Reef (CLR). This was done by measuring the physical properties (ultrasonic velocities and bulk densities) as well as conducting mineralogical analyses on drill-core samples. Ultrasonic measurements of P- and S-wave velocities were determined at ambient and elevated stresses, up to 65 MPa. The results show that the quartzite samples overlying and underlying the CLR exhibit similar velocities (~ 5028 m/s-5480 m/s and ~ 4777 m/s-5211 m/s, respectively) and bulk densities (~ 2.68 g/cm3 and 2.66 g/cm3). This is due to similar mineralogy and chemical compositions observed within the units. However, the CLR has slightly higher velocity (~ 5070 m/s-5468 m/s) and bulk density (~ 2.78 g/cm3) than the surrounding quartzite units probably due to higher pyrite content in the reef, which increases the velocity. The hangingwall Green Bar shale exhibits higher velocity (5124 m/s-5914 m/s) and density values (~ 2.89 g/cm3-3.15 g/cm3) compared to all the quartzite units (including the CLR), as a result of its finer grain size and higher iron and magnesium content. In the data set it is found that seismic velocities are influence by silica, iron and pyrite content as well as the grain size of the samples, i.e., seismic velocities increase with (1) decreasing silica content, (2) increasing iron and pyrite content and (3) decreasing grain size. Reflection coefficients calculated using the seismic velocities and densities at the boundaries between the CLR and its hangingwall and footwall units range between ~0.02 and 0.05, which is below the suggested minimum of 0.06 required to produce a strong reflection between two lithological units. This suggests that reflection seismic methods might not be able to directly image the CLR as a prominent reflector, as observed from the seismic data. The influence of micro-cracks is observed in the unconfined uniaxial compressive stress tests where two regimes can be identified: (1) From 0 - 25 MPa the P-wave velocities increase with progressive loading, but at different rates in shale and quartzite rocks owing to the presence of micro-cracks and (2) above stresses of ~20 - 25 MPa, the velocity stress relationship becomes constant, possibly indicating total closure of micro-cracks. The second part of the study integrates 3D reflection seismic data, seismic attributes and information from borehole logs and underground mapping to better image and model important fault systems that might have a direct effect on mining in the West Wits Line goldfields. 3D seismic data have delineated first-, second- and third-order scale faults that crosscut key gold-bearing horizons by tens to hundreds of metres. Applying the modified seismic attribute has improved the imaging of the CLR by sharpening the seismic traces. Conventional interpretation of the seismic data shows that faults with throws greater than 25 m can be clearly seen. Faults with throws less than 25 m were identified through volumetric (edge enhancement and ant-tracking seismic attributes) and horizon-based (dip, dip-azimuth and edge detection seismic attributes) seismic attribute analysis. These attributes provided more accurate mapping of the depths, dip and strikes of the key seismic horizon (Roodepoort shale), yielding a better understanding of the relationship between fault activity, methane migration and relative chronology of tectonic events in the goldfield. The strato-structural model derived for the West Wits Line gold mines can be used to guide future mine planning and designs to (1) reduce the risks posed by mining activities and (2) improve the resource evaluation of the goldbearing reefs in the West Wits Line goldfields.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand in fulfilment of the requirements for the degree of Master of Science, School of Geosciences. Johannesburg, 2016.
Keywords: Mines and mineral resources; Geology--South Africa; Seismology; Seismic reflection method; Mineralogy